Prevalence of anemia among medical students of nobel medical college and correlation with body mass index - Yadav, Renu; Ghimire, Nisha; Mukhopadhyay, Soumitra; Yadav, Subodh Kumar (Asian Journal of Medical Sciences, 2020)
Background: Studies have concluded that the medical students of hostels are at high risk of anemia due to inappropriate diet and their long schedules that indirectly affect their performance. Thus, concerning for the long duration of medical studies, it has become a serious medical issue. Aims and Objective: Thus, our objective is to determine the prevalence of anemia among medical students in Nobel Medical College and Teaching Hospital, Nepal. Materials and Methods: This is a descriptive cross-sectional study which was conducted and Teaching Hospital from January 2017 to December 2017 where all the subjects were selected with convenient sampling technique. The total of 150 MBBS students (male=95, female=55), age 18-25 years were included in the study who were clinically healthy. The demographic data (name, age, sex, address) and anthropometric variables (height, weight, body mass index) were recorded and hemoglobin was estimated by Sahli’s acid hematin method. Results: Only 42.1% of total were mild anemic and 11.6 % were moderately anemic. Among female, 1.8% were severely anemic, 9.1% were moderately anemic and 41.8% were mild anemic. Compared to male, anemia in female medical students was found to be more extensive. Conclusions: It has been concluded from the above study that the mild anemia is highly prevalent among medical students regardless of gender. Though the subjects are not severely affected, it is a concerned issue since the cause might be inappropriate food habit or the food facilities available at hostels.